A Qualitative Study of Unplanned Hospital Readmissions: Patient Perspectives on Their Hospital to Home Transition - Dale Yeatts; Chetan Tiwari; Samuel Coleman; Michelle Yeatts; Katherine Sobering (Nursing Reports, 2025)
Background: Roughly 18% of all patients discharged from hospitals in the United States experience an unplanned hospital readmission (UHR) within 30 days of discharge. This can be life-threatening for patients and costs the U.S. health care system billions of dollars. The Centers for Medicare and Medicaid Services is seeking continued research to identify factors contributing to UHR. Research has viewed the transition from hospital to home in three stages: the pre-discharge stage where the patient is being diagnosed and treated in the hospital, the bridging stage where the patient is being prepared for discharge, and the post-discharge stage where the patient is recovering at home. Objectives: Our aims were: (1) to identify factors perceived by patients to influence their recovery during at least one of the three stages of the hospital to home transition and (2) to identify factors perceived by patients as important across all three stages of the transition. Methods: To accomplish this, we analyzed information obtained from in-depth, home interviews with 62 participants who had been discharged from a regional hospital roughly 30 days prior to the interview. Our analysis included open-ended readings and the use of qualitative analysis software. Results: Factors reported to influence recovery at the pre-discharge stage include appropriate diagnosis, treatment, and financial resources. Factors at the bridging stage include access to health information and social supports. Factors perceived to influence recovery at post-discharge include personal characteristics, social supports, and the environment. Conclusions: Participants identified factors at the pre-discharge, bridging, and post-discharge stages believed to be influencing their ability to recover from a hospital stay. Four of these factors were perceived to influence their recovery across multiple stages of the hospital to home transition. These included financial resources, social supports, access to health services, and personal stress.